QUANTITATIVE DIFFERENCES IN ACQUIRING THE MOTOR TESTS WITH STUDENTS FROM THE REPUBLIC OF MACEDONIA AND REPUBLIC OF SERBIA - Georgi Georgiev; Žarko Kostovski; Viktor Mitrevski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The research has been conducted on two sub-samples of male gender from the Republics of Macedonia and Serbia, aged from 14 to 15 years (±3 months) who had their training classes in urban areas. The number of entities participating in the tests was 119 in total. The aim is to establish if there are differences in motor abilities through acquiring the motor tests for assessing explosivity, start speed, and precisity. Statistically significant difference between the two groups is established with the estimating precisity only.